2022
DOI: 10.3847/1538-4357/ac450a
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Accretion onto Herbig Ae/Be Stars Using the Brγ Line

Abstract: Accretion plays an important role in protoplanetary disk evolution, and it is thought that the accretion mechanism changes between low- and high-mass stars. Here we characterize accretion in intermediate-mass, pre-main-sequence Herbig Ae/Be (HAeBe) stars to search for correlations between accretion and system properties. We present new high-resolution, near-infrared spectra from the Immersion GRating INfrared Spectrograph for 102 HAeBes and analyze the accretion-tracing Brγ line at 2.166 μm. We also include th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 95 publications
3
18
0
Order By: Relevance
“…We suspect that the small difference between both groups is caused by the lower resolution of our observations, which moved many P-Cygni and double-peak profiles to the "single-peaked" group. We point out that similar percentages were found for the Brγ line by Grant et al (2022) in known Herbig stars.…”
Section: Emission Lines and Accretion Ratessupporting
confidence: 86%
See 3 more Smart Citations
“…We suspect that the small difference between both groups is caused by the lower resolution of our observations, which moved many P-Cygni and double-peak profiles to the "single-peaked" group. We point out that similar percentages were found for the Brγ line by Grant et al (2022) in known Herbig stars.…”
Section: Emission Lines and Accretion Ratessupporting
confidence: 86%
“…The break between both groups was set at -+ 3.98 0.94 1.37 M e . This accretion break and similar accretion gradients to those found in Wichittanakom et al (2020) have also been identified by Grant et al (2022), using a similar sample and the Brγ line as the accretion tracer.…”
Section: Accretion Propertiessupporting
confidence: 80%
See 2 more Smart Citations
“…There is still a controversy about the evolutionary classification of all of them. In some studies they are considered pre-main-sequence Herbig Be stars (e.g., [75][76][77] to name a few recent ones), but there has not been an unambiguous conclusion as to their extreme youth. Neither of these objects belongs to a star-forming region or has a strong far-IR excess from distant CS dust radiation that is similar to those of true pre-main-sequence stars.…”
Section: Suspected But Unconfirmed Binariesmentioning
confidence: 99%